españolImpact of the life reform program in the prevention of hepatic steatosis city of Chachapoyas - Quispe Narvaez, Manuel Jesus (2020)
Objective: To evaluate the impact of the life reform program in the prevention of hepatic steatosis in teachers and administrators of this population. Method: The approach was quantitative, quasi - experimental methodology with a single group with pre- and post-test, with a representative sample of 64 teachers from regular basic level educational institutions in the city of Chachapoyas Amazonas network. Main Results: The results revealed that the life reform program showed a decrease in the levels of hepatic steatosis, which is why its affinity in preventing it is inferred; in the teachers of the three educational institutions of the City of Chachapoyas, Amazonas - Peru: San Juan of the Libertad (P = 0.006), Seminario Jesús María (P = 0.01) and Virgen of Asunta (P = 0.01) with a 95% confidence, denoting the changes before and after the intervention. Conclusion: It concludes with the proposal of the Rainbow Cosmic Care Theory, which integrates a collaborative, multidisciplinary work of sectorial gear to achieve integral human health with a healthy environment in these times.